(untitled) (Journal of Educational Sciences, 2025)
The article examines school–family partnership in shaping the legal culture of senior secondary students within the context of values-oriented education. The study is based on a comparative analysis of Kazakhstan’s experience against educational models in Finland, Turkey, and South Korea. In international research, family–school partnership is identified as a key factor in the development of students’ civic and legal awareness, whereas in Kazakhstan’s education system this process is currently at the stage of active implementation. Over the past three years (2023–2025), international publications (Wiley, MDPI, SAGE) have presented the “school – family – community” triad as an effective model for legal education. The article proposes a pedagogical model for developing legal culture grounded in value-based principles, intersectoral interaction, and social partnerships. Particular attention is given to the role of parents, teachers, and the community in fostering students’ legal thinking, civic responsibility, and culture of conduct. In the practical part of the study, 110 respondents from the city of Taraz participated, including 60 students, 30 parents, and 20 teachers. The study has practical significance for improving the system of legal education and integrating values-oriented approaches into modern education in Kazakhstan. The findings broaden understanding of the mechanisms for shaping legal culture amid the renewal of school curriculum content. It is shown that sustainable development of legal awareness is possible only when the educational influences of school and family are united. The proposed methodological solutions can be applied in teacher education universities and within professional development systems for educators. The conclusions confirm the need for systematic implementation of partnership models in the national strategy of civic and legal education. Keywords: legal culture, school-family partnership, value-based education, comparative analysis, civic consciousness, legal education.